DAMPAK KECEMASAN PADA ATLET BOLA BASKET SEBELUM BERTANDING - Ardiansyah, Boby (Jurnal Phederal Penjas, 2014)
There search was conducted t odetermine the impact of anxiety on basket ball athletes before competing. This research used qualitative research methods to the case study approach. Determination of the subjectis done by using th etechnique of Extreme Sampling. Subjects consisted of three basketball athletes which have higher anxiety than fifteen basket ball athletes in basket ball club Bima Sakti Malang.Data collection techniques using semi-structured interviews, non-participant observation, anddocumentation. Theresultsof thisresearch istheimpact ofanxiety on basket ball athletes before competing caused by impaire dattention and concentration the naffec to ther psychicsymptoms. Physicalsymptoms arise due to thein fluenceof psychologicalsymptoms of anxiety and then have animpacton the basket ball athletes before competing.